2013
DOI: 10.1590/s1516-14392013005000067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different acid etchings on the superficial characteristics of Ti sandblasted with Al2O3

Abstract: Some implant manufactures use Al 2 O 3 instead TiO 2 powder to sandblast the machined dental implant, because Al 2 O 3 powder is commercially more easily available and is cheaper than TiO 2 powder. However, Al 2 O 3 powder usually leaves aluminum oxide contamination on the surface, which is potentially toxic. In this work, we subjected Ti discs previously sandblasted with Al 2 O 3 powder to 5 different acid etchings in order to verify which treatment is able to remove incorporated particles of Al 2 O 3 from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Comparing the present roughness parameters results with the ones obtained by Chrcanovic et al 21 , it can be observed that the values did not significantly differ in groups AT2, AT3, and AT4. When this is taken into account it can be suggested that for these acid etching groups, at least when considering the amplitude roughness parameters, there is no need to perform the sandblasting procedure before the acid treatment in order to increase the roughness of the surface; only the acid etching treatment could be enough.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Comparing the present roughness parameters results with the ones obtained by Chrcanovic et al 21 , it can be observed that the values did not significantly differ in groups AT2, AT3, and AT4. When this is taken into account it can be suggested that for these acid etching groups, at least when considering the amplitude roughness parameters, there is no need to perform the sandblasting procedure before the acid treatment in order to increase the roughness of the surface; only the acid etching treatment could be enough.…”
Section: Discussionsupporting
confidence: 74%
“…This method has advantages compared with current methods of roughening such as grit blasting, plasma spraying, and beads. As the production process does not stress the adjacent material, there is no risk of flaking or delamination and the process does not leave particles of grit 20,21 . All test groups have been acid attacked; nevertheless, due to the distinct treatment parameters, every implant displayed distinct surface roughness characteristics and a proper surface aspect that could not be mistaken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium with different surface modifications shows a wide range of chemical/physical properties and surface topographies/ morphologies, depending on how they are prepared and handled (Chrcanovic et al, 2012;Chrcanovic et al, 2013), and it is not clear whether, in general, one surface modification is better than another (Wennerberg and Albrektsson, 2009;Wennerberg and Albrektsson, 2010). These variables may have affected the outcome-and not just the subjection of the insertion of implants in patients who had diabetes or not.…”
Section: Discussionmentioning
confidence: 99%
“…The method may have advantages compared with some other methods of roughening such as grit blasting, plasma spraying, and beads. As the process does not stress the adjacent material, there is no risk of flaking or delamination, thus leaving particles of grit [6][7][8] . It has been suggested that the surface modification of titanium by acid etching has a positive effect on endosseous integration.…”
Section: Introductionmentioning
confidence: 99%